Enlargement of choroid plexus in complex regional pain syndrome - Zhou, Guangyu (Sci Rep, 2015)
The choroid plexus, located in brain ventricles, has received surprisingly little attention in clinical neuroscience. In morphometric brain analysis, we serendipitously found a 21% increase in choroid plexus volume in 12 patients suffering from complex regional pain syndrome (CRPS) compared with age- and gender-matched healthy subjects. No enlargement was observed in a group of 8 patients suffering from chronic pain of other etiologies. Our findings suggest involvement of the choroid plexus in the pathogenesis of CRPS. Since the choroid plexus can mediate interaction between peripheral and brain inflammation, our findings pinpoint the choroid plexus as an important target for future research of central pain mechanisms.